Making Circularity Actionable - An Interaction Design Approach to Identifying Demands and Developing a Digital Circular Business Model Tool for Furniture SMEs - Bökmark, Lina; Ekstedt, Amanda (My University, 2026)
This thesis explores how a digital tool can support small- and medium-sized enterprises (SMEs) in the furniture industry in developing circular business models (CBMs). Using a Research through Design approach within a Double Diamond framework, the study combines interviews, iterative prototyping, and usability testing to identify both organizational needs and interaction design demands. The findings show that furniture SMEs are generally motivated to work with circularity, but often lack structure, guidance, and decision support in the transition process. Based on these insights, a high-fidelity prototype was developed and evaluated. Key design demands included stepwise guidance, concrete decision support, and accessibility for users with low digital maturity. The study suggests that digital tools can make circular business model development more accessible by transforming complex strategic decisions into understandable and actionable processes. The value of the tool was found not only in its outcomes, but in supporting learning, reflection, and collaboration throughout the transition process.
Keywords: Interaction design, usability, digital tool, circularity, circular economy, business model development, furniture SMEs